Subverting Poetic Eroticism: Raising Awareness of the Word which Excludes the Monogamous System - Lema París, Ánxela (Madrygal. Revista de Estudios Gallegos, 2025)
This article studies the influence of the "monogamous system" (Vasallo, 2018) and the biography of the authorial figure as ideological mediators in the process of reading erotic poetry. Poetic voices appear to be sexualized according to the sex-gender system (Lauretis, 2013), as well as the sexual orientation (always interpreted as monosexual) and the interpersonal relationships (in most cases assumed to be monogomous) of the author. The analysis focuses on the critical reception of six poetry collections by different authors published between 2000 and 2010 to gain an in-depth understanding of the discourse around pleasures and affects that circulates in the field of literature. At the same time, it directly engages the poems to reveal the new poetic meanings that could be obtained if one were to truly accept the fictional pact (Eco, 1985, 1987) of literature. These rereadings will dialogue with the proposals of authors such as Rich (1996), Esteban (2011), Mogrovejo (2016), among others. They will confirm how the deconstruction of the reading vision and the adoption of a non-monogamous feminist perspective can shed light on the existence of a multi-affective Galician erotic poetry, one that remains hidden due to a thinking founded on hegemonogamia (Rosso, 2009) and on a monosexism that refuse bisexual reality (Lucio, 2019)
Keywords: Erotic poetry; Authorship; Sex-gender system; Sexuality; Monogamy